A human scFv antibody that targets and neutralizes high molecular weight pathogenic amyloid‐β oligomers. Issue 6 (2nd August 2017) - Sebollela, Adriano; Cline, Erika N.; Popova, Izolda; Luo, Kevin; Sun, Xiaoxia; Ahn, Jay; Barcelos, Milena A.; Bezerra, Vanessa N.; Lyra e Silva, Natalia M.; Patel, Jason; Pinheiro, Nathalia R.; Qin, Lei A.; et al.
Abstract : Many different species of Aβ oligomers (AβOs) have been identified in the Alzheimer's diseased brain but it is unclear which of these species are most relevant to the disease. Here we describe a single chain antibody (scFv), NUsc1, that preferentially targets a subset of AβO species. Neutralization of these species by incubation with NUsc1 prevents the AD hallmarks of Tau hyperphosphorylation and oxidative stress. Thus, NUsc1 may be considered a strong new candidate for anti‐Alzheimer therapeutics. Abstract: Brain accumulation of soluble oligomers of the amyloid‐β peptide (AβOs) is increasingly considered a key early event in the pathogenesis of Alzheimer's disease (AD). A variety of AβO species have been identified, both in vitro and in vivo, ranging from dimers to 24mers and higher order oligomers. However, there is no consensus in the literature regarding which AβO species are most germane to AD pathogenesis. Antibodies capable of specifically recognizing defined subpopulations of AβOs would be a valuable asset in the identification, isolation, and characterization of AD‐relevant AβO species. Here, we report the characterization of a human single chain antibody fragment (scFv) denoted NUsc1, one of a number of scFvs we have identified that stringently distinguish AβOs from both monomeric and fibrillar Aβ. NUsc1 readily detected AβOs previously bound to dendrites in cultured hippocampal neurons. In addition, NUsc1 blocked AβO binding and reduced AβO‐induced neuronal oxidative stress and tau hyperphosphorylation in cultured neurons. NUsc1 further distinguished brain extracts from AD‐transgenic mice from wild type (WT) mice, and detected endogenous AβOs in fixed AD brain tissue and AD brain extracts. Biochemical analyses indicated that NUsc1 targets a subpopulation of AβOs with apparent molecular mass greater than 50 kDa. Results indicate that NUsc1 targets a particular AβO species relevant to AD pathogenesis, and suggest that NUsc1 may constitute an effective tool for AD diagnostics and therapeutics.